2010
DOI: 10.1002/zoo.20280
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal shifts in giant panda feeding behavior: relationships to bamboo plant part consumption

Abstract: The giant panda (Ailuropoda melanoleuca) is classified as a carnivore, yet subsists on a diet comprised almost exclusively of bamboo. Wild and captive giant pandas use highly selective foraging behaviors for processing and consuming bamboo. These behaviors are for the first time quantified in captive giant pandas over a 5-year period of time showing highly specific seasonal trends. Giant panda feeding behavior was recorded using live video observations of two giant pandas housed at the Memphis Zoo from Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Hansen et al [2009] found that captive giant pandas at the Memphis Zoo primarily consumed leaves June-December, whereas culm was consumed primarily February-May. It might be that the male panda had not yet switched to eating leaves in trial ]6 (June), whereas the switch had been made by the pandas in trials ]1-3 (August through November).…”
Section: Discussionmentioning
confidence: 98%
“…Hansen et al [2009] found that captive giant pandas at the Memphis Zoo primarily consumed leaves June-December, whereas culm was consumed primarily February-May. It might be that the male panda had not yet switched to eating leaves in trial ]6 (June), whereas the switch had been made by the pandas in trials ]1-3 (August through November).…”
Section: Discussionmentioning
confidence: 98%
“…Due to such factors as season, transportation, weather, etc., captive giant pandas are generally provided with only one species of bamboo. Thus, pandas in captivity primarily eat shoots in spring, leaves in summer and fall, and culms in winter and early spring before the shoots grow in the next cycle 5 . Adult giant pandas are provided with several kinds of bamboo species each year 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…For much of the year, giant pandas feed primarily on the leaves of bamboo. However, giant pandas in some sub-populations have been reported to consume a large proportion of culm during the late winter/early spring months and switch back to leaves in mid- to late June [9, 11, 14, 15]. During the bamboo growth season in spring, shoots are eaten almost exclusively.…”
Section: Introductionmentioning
confidence: 99%
“…Although changes in foraging behavior for captive and wild giant pandas have been described to be a response to changes in bamboo nutrient composition [9, 11, 15, 16], the nutrient, or combination of nutrients, driving species and plant part selection by giant pandas is largely unknown. At the Memphis Zoo, giant pandas exhibited a dietary preference for culm during spring followed by a dietary shift to greater leaf consumption in mid-summer that was similar to many of their wild counterparts [15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation